Macroeconomic Stability in a Model with Bond Transaction Services - Massimiliano Marzo; Paolo Zagaglia (International Journal of Financial Studies, 2018)
Cochrane (2014) shows that high-powered money balances and short-term government bonds can be considered as perfect substitutes for the U.S economy during the past twenty years. We build on this claim and consider a variant of the standard cashless new-Keynesian model with two types of government bonds, which can be thought of as short- and long-term bonds. The first one has a macroeconomic role in the sense that it provides transaction services in addition to generating a yield. The other type of government bond pays only an interest rate. Consistent with previous findings, the Taylor principle is not a panacea for equilibrium determinacy in a model without money. When the government bond market matters beyond the need for fiscal solvency, monetary policy rules do not need to comply with the Taylor principle for unique equilibria to exist.